Chapter Five: Massacres. Sociologie des violences de masse - Glasman, Joël (Humanities for Humanitarians. An Experiment in the Public Implications of Multiple Ontology, 2024)
This is the Bibliography of the book Petit manuel d’autodéfense à l’usage des volontaires Les humanités humanitaires. To cite: Glasman, Joël. Petit manuel d'autodéfense à l'usage des volontaires: Les humanités humanitaires. Paris: Les Belles Lettres, 2023.
Keywords: Massacres; Violence; Humanities; Humanitarian Studies; Humanitarian